Development of DOAS System for Hazardous Methane Detection in the Near-Infrared Region - Khandaker, Sayma; Hasan, Md Mahmudul; Shaipuzaman, Nurulain; Aspar, Mohd Amir Shahlan Mohd; Manap, Hadi (EMITTER International Journal of Engineering Technology, 2024)
Methane (CH4) is a powerful greenhouse gas that greatly contributes to global warming. It is also very combustible, which means it has a large danger of causing explosions. It is crucial to tackle methane emissions, especially those arising from oil and gas extraction processes like transit pipes. An area of great potential is the advancement of dependable sensors for the detection and reduction of methane leaks, with the aim of averting dangerous consequences. An open-path differential optical absorption spectroscopy (DOAS) system was described in this paper for the purpose of detecting CH4 gas emission at a moderate temperature. An in-depth examination of the absorption lines was conducted to determine the optimal wavelength for measurement. The Near Infrared (NIR) region was identified as the most suitable wavelength for detecting methane. Multiple measurements were conducted at different integration times (1 second, 2 seconds, and 3 seconds) to ensure reliability and determine the optimal integration time for the CH4 detection system. The DOAS system has the capability of precisely detecting methane concentrations at 1M ppm in the NIR region with a quick integration time of 2 seconds.